Influence of main beam parameters stability on beam size measurements at PITZ - Spesyvtsev, R. (Вопросы атомной науки и техники, 2007)
The photo injector test facility in Zeuthen (PITZ) is used to develop and characterize electron sources which produce a nominal bunch charge of 1 nC with the lowest possible transverse emittance. Measurements of the beam size provide us with knowledge on important beam characteristics. For example the measurement of the emittance is based on beam size measurements. Therefore, the control of uncertainties of beam size measurements is very important to validate the experimental results. The statistical uncertainty of transverse beam size measurements due to the beam energy and bunch charge jitters is considered in this paper. Стенд випробувань фотоінжекторів PITZ використовується для розробки та вивчення характеристик джерел електронів, що випромінюють пучки з номінальним зарядом в 1 нКл та якомога меншим емітансом. Одним з базових вимірів є вимір поперечного розміру електронного пучка. Наприклад вимірювання емітансу базується на вимірах розміру пучка. Таким чином врахування невизначеності вимірів розміру пучка є важливим для визначення вірогідності експериментальних результатів. В даній роботі розглянута статистична невизначеність виміру поперечного розміру електронного пучка в PITZ. Стенд испытания фотоинжекторов PITZ служит для разработки и характеризации источников электронов, которые способны производить пучки с номинальным зарядом в 1 нКл и малым поперечным эмиттансом. Одним из базисных измерений при характеризации фотоинжектора является измерение поперечного размера электронного пучка. В частности, измерение поперечного эмиттанса основано на измерениях размера пучка. Знание погрешности в измерении размера пучка является очень важным условием для определения достоверности экспериментальных результатов. В данной работе рассмотрена статистическая неопределенность в измерении поперечного размера электронного пучка, вызванная флуктуациями энергии и заряда пучка.